Comparing The Anthropometric Measurements of Intra-Extra Uterine Period between Stunting and Non-stunting Children Aged 6-24 Months Old in Bogor Tengah Subdistrict, Bogor City, West Java - christina olly lada; Jose Rizal Batubara; Saptawati Bardosono; Anies Irawati; Salimar Salimar (World Nutrition Journal, 2019)
Introduction: The prevalence of stunting in children under two years old is high in developing country. Stunting in the early of life has many negative health consequences in later life, while the positive view is stunting could be prevent earlier by detecting a predisposing factors in intrauterine and extrauterine periode. Anthropometry of intrauterine predisposing factors (IntraPF) and Extrauterine predisposing factors (ExtraPF) could detect growth retardation. These study aim was to prove that there were significant different of IntraPF and ExtraPF between stunting and non stunting children aged 6-24 months.Methods: This comparative cross sectional study was nested to (Bogor longitudinal study on child growth and development (BLSCGD) held by National Health Research and Development (NHRD), Health Ministry of Indonesia. Subjects who defined as stunting if their height for age was more than two standard deviations below the WHO Child Growth standards median. There were 38 stunting and 46 non-stunting aged 6-24 months who met the study criteria. Independent variable was (1)IntraPF follow as maternal height, weight and length of neonatal, (2)ExtraPF: weight gain and body length gain at first six months of neonatal. Primary and secondary data collection was carried out from July 2017 to Februari 2018, held at the BLSCGD. All of body measurement using WHO standard.  Appropriate statistical analysis was used to compare the stunting and non-stunting groups with a significance limit of p <0.05.Results: Statistical analysis tests showed that: significantly different and lower IntraPF in the stunting group was maternal height, birth weight and length of the subjects compare to non-stunting and there were significant different and lower of ExtraPF follow as weight gain in the first six months, average weight gain per month in the first six months, increase in body length in the first six months, average increase in body length every month in the first six monthssignificantly lower in stunting children compare to non stunting children.Conclusion: The antropometric of intrauterine, extrauterine predisposing factors have been showed to have an impact on the child's height. It is important to monitor the anthropometry of the mother before pregnancy and provide nutritional interventions in the first 1000 days